A whale of a time! An experience-based typology of visitors to a South African whale-watching festival. (December 2018) - Kruger, Martinette; van der Merwe, Peet; Saayman, Melville
Abstract: This research segments whale watchers in South Africa according to the factors regarded as important for a memorable experience by these natural event viewers. The segmentation gives an ACC-typology of viewers, namely abundant experience seekers, convenience experience seekers and comprehensive experience seekers . The results show that such segmentation is a useful research tool for producing a clear visitor profile, enabling us to provide strategic insights into managing the whale viewing experience, as well as similar natural events, according to the preferences of specific market segments. The findings, however, shows that the Hermanus Whale Festival has to revise the current management and marketing strategy to emphasise the natural phenomenon of the whale migration as the primary festival attraction and the 'festivalscape' elements surrounding entertainment as ancillary to the visitor experience. This management approach is recommended to these types of festivals that are organised around natural events, as it is vital that these events remain true to their initial objective of educating visitors about the natural phenomenon and the conservation thereof.